ANTIANEMIA SUPPLEMENTATION COMBINATION WITH VITAMIN C ON HEMOGLOBIN LEVELS AMONG PREGNANT WOMEN IN PRIMARY HEALTH CARE CENTER, JEPARA, INDONESIA - Poppy Diah Palupi; Mohammed Safwan Ali Khan; Kukilo Kenuk Karseno (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2021)
Blood volume escalation during pregnancy leads to an increase in iron needs. Pregnant women are prone to maternal anemia that is caused by iron, folic acid, vitamins B2, B12, A, and C deficiency and may serve as causative factors that aggravate anemia. Concerning the problem, this clinical investigation determined the effect of antianemia supplementation and its combination with vitamin C on hemoglobin levels during pregnancy. This study is a quasi-experimental involving 34 patients who consumed antianemia supplements with or without vitamin C. The treatment group was given a combination of antianemia supplement Fe Fumarate 180 mg-Folic Acid 400 mcg and vitamin C 100 mg. The positive-control group was administrated with antianemia supplement Fe Fumarate 180 mg-Folic Acid 400 mcg. After 28 days, blood samples were taken to measure the hemoglobin levels. The hemoglobin levels were found to have a statistically significant difference (p0.05) between that group receiving a combination of antianemia-vitamin C and the other group administered with antianemia alone.